Hepatic patatin‐like phospholipase domain‐containing 3 levels are increased in I148M risk allele carriers and correlate with NAFLD in humans - Elke Ericson; Linnéa Bergenholm; Anne‐Christine Andréasson; Carly I. Dix; Jane Knöchel; Sara F. Hansson; Richard Lee; Jennifer Schumi; Madeleine Antonsson; Ola Fjellström; Patrik Nasr; Mathias Liljeblad; et al. (Hepatology Communications, 2022)
Abstract In nonalcoholic fatty liver disease (NAFLD) the patatin‐like phospholipase domain‐containing 3 (PNPLA3) rs738409 variant is a contributor. In mice, the Pnpla3 148M variant accumulates on lipid droplets and probably leads to sequestration of a lipase cofactor leading to impaired mobilization of triglycerides. To advance our understanding of the localization and abundance of PNPLA3 protein in humans, we used liver biopsies from patients with NAFLD to investigate the link to NAFLD and the PNPLA3 148M genotype. We experimentally qualified an antibody against human PNPLA3. Hepatic PNPLA3 protein fractional area and localization were determined by immunohistochemistry in biopsies from a well‐characterized NAFLD cohort of 67 patients. Potential differences in hepatic PNPLA3 protein levels among patients related to degree of steatosis, lobular inflammation, ballooning, and fibrosis, and PNPLA3 I148M gene variants were assessed. Immunohistochemistry staining in biopsies from patients with NAFLD showed that hepatic PNPLA3 protein was predominantly localized to the membranes of small and large lipid droplets in hepatocytes. PNPLA3 protein levels correlated strongly with steatosis grade (p = 0.000027) and were also significantly higher in patients with lobular inflammation (p = 0.009), ballooning (p = 0.022), and significant fibrosis (stage 2–4, p = 0.014). In addition, PNPLA3 levels were higher in PNPLA3 rs738409 148M (CG, GG) risk allele carriers compared to 148I (CC) nonrisk allele carriers (p = 0.0029). Conclusion: PNPLA3 protein levels were associated with increased hepatic lipid content and disease severity in patients with NAFLD and were higher in PNPLA3 rs738409 (148M) risk allele carriers. Our hypothesis that increased hepatic levels of PNPLA3 may be part of the pathophysiological mechanism of NAFLD is supported.